Sport participation, acculturative stress, and depressive symptoms among international college students in the United States - Yim, Hyosoon; Kim, Amy Chan Hyung; Du, James; James, Jeffrey D. (Frontiers in Psychiatry, 2023)
Abstract The distinctive social nature of sport in its capacity to promote immigrants' adaptation to the new society has been regarded as a vehicle to cope with adverse mental health outcomes derived from acculturative stress and feelings of marginalization. However, the evidence on the relationship between sport participation, acculturative stress, and mental health have been lacking and fragmented. Recognizing this challenge, we examined the mediating effect of acculturative stress on the relationship between sport participation and depressive symptoms among international college students in the US. A total of 203 international college students in the United States were recruited via Prolific. The instrumentation included previously validated measures: sport participation (SLIM-18), acculturative stress (ASSIS), depressive symptoms (CES-D-10), sense of coherence (SOC-13), and demographic characteristics. Mediation analysis showed a significant association between (1) sport participation and depressive symptoms (ß = -.030, p < .05) and (2) acculturative stress and depressive symptoms (ß = .053, p < .001), while (3) no significant indirect effect of acculturative stress was found (ß = -.001, SE = .0003, 95% CI [-.008, .004]). Even though several previous scholars have argued that sport participation is an effective tool to cope with acculturative stress among international students, the present study implies this may not be applied to all international students. Specifically, acculturative stress and depressive symptoms among European participants were lower than those from non-European countries, including Asia. Future studies using meta-analysis could be beneficial to examine the external validity of the previous studies on the relationship between sport participation, acculturation, and mental health to address this potential heterogeneity on the level of acculturative stress based on their origin countries or continents. The current study provides meaningful implications for adopting the transformative marketing perspective, which is a marketing approach that pursues positive social outcomes by promoting positive behavior of the target population